Image reconstruction for remote photoacoustic tomography using speckle-analysis - Lengenfelder, Benjamin; Hohmann, Martin; Röhm, Margarete; Schmidt, Michael; Zam, Azhar; Zalevsky, Zeev; Klämpfl, Florian (Proceedings Volume 11363, Tissue Optics and Photonics; 113631F (2020), 2020)
Photoacoustic tomography is a new, rising imaging technique since it combines high penetration depth with good image contrast. Speckle-analysis represents an attractive, non-contact alternative to contact-based ultrasound transducers which are state of the art for photoacoustic tomography. In this work, it is demonstrated for the first time that the speckle-sensing technique is in theory capable of photoacoustic image reconstruction by measuring on several surface locations after photoacoustic excitation. Therefore, a simulative model is used to test a back-reconstruction algorithm and a first feasibility experiment is show
Keywords: Photoacoustic; remote sensing; image reconstruction